Knowledge and perspective of artificial intelligence in dentistry among dentists and dental students: A cross sectional study - Iqbal, Kanwal; Abidi, Fizza; Fatima, Sana; Amir, Alina; Altaf, Yousra; Nauman, Ammarah Muhammad (Journal of Rawalpindi Medical College, 2025)
Objective: In some areas of dentistry, artificial intelligence (AI) is the newest buzzword. This study set out to evaluate knowledge and perspective of AI among dental students and professionals of Ziauddin University, Karachi, Pakistan. Methods: The study employed a validated self-reported questionnaire in a cross-sectional design to assess 250 dental students and dentists of Ziauddin University. Results: A total of 84% of respondents said that they understood what AI is, and 77.2% said they were somewhat familiar with its applications in dentistry. Overall 75.6% of participants agreed or strongly agreed that AI will result in significant advancements in dentistry. On the other hand, 59.2% disagreed or strongly disagreed that dentists would ever be replaced by AI. Dentists scored considerably higher on attitude than dental students, although there were no gender-specific differences. Conclusion: The dental faculty and dental students at Ziauddin University are generally positive in their perceptions towards artificial intelligence in dentistry and have a reasonable level of awareness of it. Though, AI is not used much in reality. Given the global shift to digitalization, AI must be included in dentistry curricula.